Rosário dos kamburekos : espirais de cura da ferida colonial pelas crianças negras no Reinadinho (Oliveira-MG) - Bárbara Regina Altivo (2019)
This thesis is based on the spiritual, affective and intellectual relations that I developed in the field with the brotherhood of Reinado "Os Leonídios" and the group of black children that form the so-called “reinadinho” in Oliveira-MG. I approach the Reinado as a vast and complex cosmological, subjective, social and political work of healing relationships torn apart by slavery and racism, through inventive operations that put into communication different beings, times and languages. The dive in this process occurred through the encounter with children's thought-action through classic ethnographic strategies such as observation, participation, personal interviews, maintenance of a fiel journal, audiovisual records and varied workshops. In addition, I approached the Reinado in a corporal and affective way, experiencing mediumistic trances that connected me singularly to the community and the children. By engaging ethnographic experience and academic theories, a black, decolonial and childlike cosmopolitics is articulated, which allows for the discovery of the main ways of self-rearing black childhood em the “reinadinho”: 1) the magical repopulation of the cosmos in the "kambureko house", founding a existential territory proper for the remains and ruins of the adults on the edges of the black periphery of the town; 2) the sensitivity to the ancestral souls and deities, constituting a black community that reconnects ruptured bonds by the slavery diaspora when crossing the plane of the alive and the dead, enablig the circulation of knowledge and affections by the lineages of African matrix; and 3) the performative skills and knowledge of children, acting in the production of a memory and a black history through the body, through the seams of narrative, imagery and affective fragments, by deconstructing colonial language and establishing multimensional forms of communication. In order to account for the richness of this encounter, the thesis takes the form of a dialogical device that brings together notes and field images, ethnographic descriptions, conceptual of academic verve and interventions of Brazilian black art.